Differing roles for zinc fingers in DNA recognition: Structure of a six-finger transcription factor IIIA complex - Nolte, Robert T. (The National Academy of Sciences, 1998)
The crystal structure of the six NH(2)-terminal zinc fingers of Xenopus laevis transcription factor IIIA (TFIIIA) bound with 31 bp of the 5S rRNA gene promoter has been determined at 3.1 Å resolution. Individual zinc fingers are positioned differently in the major groove and across the minor groove of DNA to span the entire length of the duplex. These results show how TFIIIA can recognize several separated DNA sequences by using fewer fingers than necessary for continuous winding in the major groove.